Oxidant and Antioxidant Status in Children With Subacute Sclerosing Panencephalitis - Caksen, Huseyin; Ozkan, Mustafa; Cemek, Mustafa; Cemek, Fatma (SAGE PUBLICATIONS INC, 2014)
We analyzed serum alpha-tocopherol, beta-carotene, retinol, and ascorbic acid levels and malondialdehyde and reduced glutathione concentrations on erythrocyte and cerebrospinal fluid in 30 patients with subacute sclerosing panencephalitis to evaluate oxidant and antioxidant status. Serum alpha-tocopherol, beta-carotene, retinol, ascorbic acid levels, and erythrocyte and cerebrospinal fluid reduced glutathione concentrations were decreased; however, erythrocyte and cerebrospinal fluid malondialdehyde levels were increased in the patients. Cerebrospinal fluid malondialdehyde levels were different between clinical stages of the disease (P < .05). Higher cerebrospinal fluid malondialdehyde level was associated with the more severe clinical stage. A positive correlation was found between cerebrospinal fluid malondialdehyde level and clinical stages (r = 0.42; P < .05) and between erythrocyte malondialdehyde level and clinical stages (r = 0.40; P < .05). Our findings showed presence of oxidative damage in subacute sclerosing panencephalitis and that antioxidants were increased as defense mechanisms of the organism against oxidative damage.
Keywords: oxidant; antioxidant; subacute sclerosing panencephalitis; INTERFERON; PATHOGENESIS; SEIZURES; STRESS; Neurosciences & Neurology; Pediatrics